Water-dispersed conjugated polyelectrolyte for visible-light hydrogen production - Dai, Chunhui (2020)
Conjugated polymer-based photocatalysts have shown great potential in H2 production via water splitting, but an intrinsic drawback of conventional hydrophobic polymer photocatalysts is their poor wettability and relatively large particle size in aqueous media, which is favorable for charge recombination with limited interfacial reaction efficiency. Herein, a well-dispersed organic water reduction system using cationic conjugated polyelectrolyte as the photocatalyst has been reported for the first time. In comparison to a model polymer (PFBT) bearing the same conjugated backbone, the polyelectrolyte exhibits significantly enhanced photocatalytic efficiency due to the extended light absorption and improved charge separation of the polymer aggregates.